Banana Peels (Musa paradisiaca L.) Extract as Phytoestrogen on Ovariectomized Mice Mammary Gland Development by Inducing c-Myc Expression - Nanda Resa Pratama; Yurista Gilang; Rita Riata; Adam Hermawan; Muthi' Ikawati; Edy Meiyanto (Indonesian Journal of Cancer Chemoprevention, 2011)
Hormone Replacement Therapy (HRT) is therapy for estrogen deficiency and post menopausal syndromes, but high cost and unwell-secured therapy. One of alternative therapy is the usage of phytoestrogens. The banana peel contains flavones, flavonol, flavanone and polimethoxyflavone which are potential as phytoestrogen. The purpose of this study was to examine the estrogenic effect of banana peel extract (BPE) development of mammary gland of ovariectomized rats. Estrogenic effects was examined based on in vivo and in silico experiment. For in vivo experiment, female Sprague-dawley rats aged 50 days were ovariectomized. At 70 days of age, 12 rats were treated with BPE 500 mg/kgBB and 1000mg/kgBB, 5 rats were treated with estradiol 2μg/day while others served as control were treated with CMC-Na 0.5% and sacrificed 2 weeks later. The base line ovariectomized rats and base line non-ovariectomized rats were sacrificed at 70 days of age. The in silico experiment examined by molecular docking between myricetin and estrogen receptor alpha (ER-α). The result of in vivo experiment showed that 1000 mg/kgBW BPE induced c-Myc expression and enhance ovariectomized rat mammary gland development significantly. Meanwhile, molecular docking showed that there are hydrogen bond interaction between bioactive compound in BPE and Estrogen Receptor (ER)-α but less powerfull than estrogen and ER-α interaction. In summary, BPE can act as an estrogen agonist, resulting in the enhancement of c-Myc expression.Keywords: banana peels extract (BPE), phytoestrogen, mammary gland, ovariectomized rats